Inhibition of PFKFB3 Hampers the Progression of Atherosclerosis and Promotes Plaque Stability - Poels, Kikkie; Schnitzler, Johan G.; Waissi, Farahnaz; Levels, Johannes H. M.; Stroes, Erik S. G.; Daemen, Mat J. A. P.; Lutgens, Esther; Pennekamp, Anne-Marije; De Kleijn, Dominique P. V.; Seijkens, Tom T. P.; Kroon, Jeffrey (Frontiers in Cell and Developmental Biology, 2020)
Aims. 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB)3-mediated glycolysis is pivotal in driving macrophage- and endothelial cell activation and thereby inflammation. Once activated, these cells play a crucial role in the progression of atherosclerosis. Here, we analyzed the expression of PFKFB-3 in human atherosclerotic lesions and investigated the therapeutic potential of pharmacological inhibition of PFKFB3 in experimental atherosclerosis by using the glycolytic inhibitor PFK158. Methods and Results. PFKFB3 expression was higher in vulnerable human atheromatous carotid plaques when compared to stable fibrous plaques and predominantly expressed in plaque macrophages and endothelial cells. Analysis of advanced plaques of human coronary arteries revealed a positive correlation of PFKFB3 expression with necrotic core area. To further investigate the role of PFKFB3 in atherosclerotic disease progression, we treated six-eight weeks old male Ldlr-/- mice. These mice were fed a high cholesterol diet for 13 weeks, of which five weeks treated with the glycolytic inhibitor PFK158 to block PFKFB3 activity. The incidence of fibrous cap atheroma (advanced plaques) was reduced in PFK158-treated mice. Plaque phenotype altered markedly as both necrotic core area and intraplaque apoptosis decreased. This coincided with thickening of the fibrous cap and increased plaque stability after PFK158 treatment. Concomitantly, we observed a decrease in glycolysis in peripheral blood mononuclear cells compared to the untreated group, which alludes that changes in the intracellular metabolism of monocyte and macrophages is advantageous for plaque stabilization. Conclusion(s). High PFKFB3 expression is associated with vulnerable atheromatous human carotid and coronary plaques. In mice, high PFKFB3 expression is also associated with a vulnerable plaque phenotype, whereas inhibition of PFKFB3 activity leads to plaque stabilization. This data implies that inhibition of inducible glycolysis may reduce inflammation, that has the ability to subsequently attenuate atherogenesis.